Sequential treatment with ursolic acid chlorophenyl triazole followed by 5-fluorouracil shows synergistic activity in small cell lung cancer cells (Bangladesh Journal of Pharmacology, 2015)
Combination therapy has prolonged the survival of patients with small cell lung cancer (SCLC), an aggressive neoplasm characterized by a high rate of metastasis. In the present study the effect of sequential treatment of ursolic acid chlorophenyl triazole (UACT) followed by 5-fluorouracil (5-FU) on human small cell lung cancer cells was investigated. The results revealed a synergistic effect of the sequential treatment with UACT and 5-FUcombination on cytotoxic activities, NF-kB protein activation, repression of TNF-induced NF-kB-dependent reporter gene expression, and TNF-induced COX-2, MMP-9 and Cyclin D1 activation in H209 cells. The synergism in apoptotic cell death was observed in H209, H69, 87-5,and Lu135 cells. The synergistic effect of UACT and 5-FU was observed at a concentration of 50 nM of UACT and 20 µM of 5-FU. These results indicate that UACT and 5-FU combination can be a promising chemotherapeutic regimen in the treatment of SCLC.